Personifikasi dalam Lirik Lagu “Mencari Cinta” dan “Menemaniku” Band Noah dalam Album Keterkaitan Keterikatan - Mujid Amin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2020)
This paper was prepared with the aim of knowing the function of the personification style in the lyrics of the song Finding Love and Menemaniku, which was created by the Band Noah. The method used in this research includes two methods, namely methods in linguistics and stylistics. The results obtained in this study are that the personified language style is a language style that can give strength to something as if it can carry out activities / actions such as activities / actions carried out by living things (animals, humans,). The personified language style has a function to describe the atmosphere as if it were real and alive, and can also bring out the atmosphere, impressions / images of certain senses; at the same time it can create beauty (aesthetics) that is in the song lyrics.